Management of soft tissues in post-extraction dental implant with connective tissue graft. Case report: Manejo de tejidos blandos en implante dental pos-extracción con injerto de tejido conectivo. Informe de un caso - Nuñez, Enrique; Torres-Tom, Suani; Espinosa-Segira, Brian; Diaz-Caballero, Antonio (Gaceta Médica de Caracas, 2025)
Dental implants are a crucial component of dentistry, and the protocols for their use are continually evolving. One crucial aspect of success is the relationship between the implant and the surrounding tissue. Grafting procedures have shown potential benefits, although limited evidence is available. This article presents a 30-year-old patient who had to undergo exodontia due to failed internal tooth bleaching that caused internal radicular resorption. Patient’s soft tissues were managed with connective tissue grafting, and a dental implant was successfully placed. Tissue grafts during immediate post-extraction implant placement are deemed effective and esthetically favorable, supporting their incorporation into clinical practice.